Investigation of the Corrosion Behavior of Selected Metal Electrodes used in a Microbial Fuel Cell for Clean Energy Production - Fayyadh, Mohammed; Köysüren, Özcan; Hasan, Basim O. (Al-Nahrain Journal for Engineering Sciences, 2025)
The electrodes material plays an important role in the amount of electricity produced in microbial fuel cells (MFCs). Metal electrodes used in MFCs are subject to biological and concentration cell corrosion which leads to a decrease in the cell efficiency. In the present work, the corrosion behavior of three selected electrode materials, namely, stainless steel, copper, and zinc under different operating conditions was investigated and discussed. In anode chamber, the microorganism (MO) used was Saccharomyces cerevisiae (yeast) with sodium acetate as a substrate forming the microbial corrosive solution. In the cathode chamber, the corrosive solution is aerated water. The effects of different operating parameters on the corrosion rate (CR) of these electrodes were studied such as: microorganism concentration, aeration of cathode chamber, and flow velocity in cathode chamber. The potential of the each electrode was measured to understand the corrosion behavior of electrodes and the produced current was also investigated. It was found that the corrosion rate of the electrodes in both anode and cathode chambers increases with increasing MO concentration in anode chamber and with increasing agitation speed in cathode chamber. The bio-corrosion is an important part of the corrosion occurring in microorganism chamber. The stainless steel exhibited the lowest corrosion rate for the whole investigated range of operating parameters followed by copper. The zinc electrode was found to be poor as an electrode in MFC as its corrosion rate was very high in all conditions investigated. In addition, this study showed that the air pumping in water chamber causes an appreciable increase in the corrosion rate in both chambers and an increase in the produced current.